The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3991/ijet.v12i05.6955
|View full text |Cite
|
Sign up to set email alerts
|

Developing Speaking Skills Using Virtual Speaking Buddy

Abstract: Abstract-This interdisciplinary study integrates ICT in education through the innovation of an interactive audio-based application as a tool to enhance English language speaking skills among less proficient students. Drawing on the sociocultural perspective of learning, the application named 'V-Buddy' has been developed and tested with a group of participants which consists of five primary school students and an English language teacher. The teacher was briefed of her role as a facilitator before the students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
(10 reference statements)
2
15
0
Order By: Relevance
“…EMP learners are in need of rich effective drilling and practice of various oral aspects, and more STT in and out of classrooms as well as using the target language more often; urging for the use of L2 as the main medium in language classrooms. This conclusion came at par with various previous studies that called for applying various techniques and using modern technology as aids to foster learners' oral production (e.g., Almoaily, 2019;Rashid et al, 2017;Yusof & Abugohar, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…EMP learners are in need of rich effective drilling and practice of various oral aspects, and more STT in and out of classrooms as well as using the target language more often; urging for the use of L2 as the main medium in language classrooms. This conclusion came at par with various previous studies that called for applying various techniques and using modern technology as aids to foster learners' oral production (e.g., Almoaily, 2019;Rashid et al, 2017;Yusof & Abugohar, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, one of the remedies explored in the present study is the often use of English as the target language in English-medium instruction (EMI) and discussions in L2. In addition, elevating learners' participation was found a pushing-forward factor for fostering students' active and interactive oral communication which was concluded a crucial critical task for second or foreign language learners, which makes this study aligned to Abugohar et al (2020), Rabab'ah (2005, Rashid et al (2017), and Yassin (2015). However, this study conclusion is inconsistent with some found literature in terms of the outcomes of English-medium instruction (e.g., Al Zumor, 2019;Joe and Lee, 2013;Sivaraman et al, 2014), who concluded that EMI impacted the acquisition and mastery of disciplinary content negatively; whereas this study supported the positive outcomes of EMI.…”
Section: Discussionmentioning
confidence: 57%
“…Research on online instructions has been extensively ongoing since over a decade, and the areas of the more recent research included students' perceptions and readiness [16]- [21]; dimensions and sub-dimensions of online learning [12], [15], [22]- [26]; factors influencing readiness [20], [27]- [28]; predictors of students' engagement and achievement in online learning [11], [13], [29]; effectiveness of online learning [30]; students' motivation and satisfaction in online learning [24], [31]- [33] ; challenges of online learning [14], [34]; and pedagogy of online classes [4], [32]- [37].…”
Section: Related Literaturementioning
confidence: 99%